A ética da tolerância como marco no constitucionalismo latino-americano - Zanon, Pedro Henrique Nascimento (2019)
This thesis is part of the Theory of Constitution in Latin America and must be emphasized that the analysis in these studies are still very much influenced from the European context, although this is also object of criticism. The Constitution is the way a society is organized politically and in the interregnum of the seventeenth and eighteenth centuries, three great European matrixes influenced the rest of the world, including Latin America. Thus, research on Latin American constitutionalism leads us to an analysis of the last 200 years, a period in which more than 100 constitutions have already been enacted in sixteen Latin American countries. The first Latin American constitutions were not innovative in terms of a social, political and philosophical aspects, and to a great extent they were influenced by the constitutional models of the colonizing States, mainly the French, American and English. Thus, in the first century of Latin American constitutionalism, was conceived the prevailing story that our constitutionalism is an ill-adapted model of the European and North American constitutional matrices. This thesis aims to deconstruct this report and show that the constitutionalism has an originality that has the ethics of tolerance as a framework. The great anguish is then to question if there really is a new Latin American constitutionalism and if there is a rupture with other matrices. Latin American society is the fruit of the cultures of indigenous peoples, blacks and Europeans and the coexistence of this diversity has allowed the development of the theory of legal pluralism and multiculturalism. These theories are based on an Andean philosophy accompanied by the ethics of tolerance. Thus, we can understand that the model of thinking about the Constitution and the State has an originality that is gestated in these factors. Thus, in order to understand what we are now, we have to reconstruct the historical course and take support in other sciences such as history, sociology, anthropology. There is a difficulty of thinking about local context without being influenced by the thoughts of Europe and the United States. That is, denying to look at reality itself and, especially, to look at the novelty of the Plurinational State in Latin America. This phenomenon can be seen as a new constitutionalist matrix, within an Andean conception of philosophy that has as its frame the ethics of tolerance. The proposal is thus to think about constitutional political existentialism and analyze the narrative that Latin America is fruit of Europe or if it is something different and original that has been built by the ethics of tolerance. In other words, this thesis analyzes whether there is a genuine perception of constitution in Latin America or whether it is still characterized as periphery of the (European) center.